2009
DOI: 10.1113/jphysiol.2009.170324
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epithelial sodium channels by cGMP/PKGII

Abstract: Airway and alveolar fluid clearance is mainly governed by vectorial salt movement via apically located rate-limiting Na + channels (ENaC) and basolateral Na + /K + -ATPases. ENaC is regulated by a spectrum of protein kinases, i.e. protein kinase A (PKA), C (PKC), and G (PKG). However, the molecular mechanisms for the regulation of ENaC by cGMP/PKG remain to be elucidated. In the present study, we studied the pharmacological responses of native epithelial Na + channels in human Clara cells and human αβγδ ENaCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 45 publications
(71 reference statements)
2
56
0
Order By: Relevance
“…CPT-cGMP, but not parent cGMP, acutely activated human ENaC activity as an external ligand (19,26). The aim of this study was to examine whether CPT-cGMP could be used as a pharmaceutical strategy to up-regulate alveolar fluid clearance (AFC) via stimulating ENaC and its underlying mechanisms.…”
Section: Epithelial Namentioning
confidence: 99%
See 1 more Smart Citation
“…CPT-cGMP, but not parent cGMP, acutely activated human ENaC activity as an external ligand (19,26). The aim of this study was to examine whether CPT-cGMP could be used as a pharmaceutical strategy to up-regulate alveolar fluid clearance (AFC) via stimulating ENaC and its underlying mechanisms.…”
Section: Epithelial Namentioning
confidence: 99%
“…A mutation (a F61L ) at the amino terminal of the protein, adjacent to the gating tract in the M1 domain, enhanced self-inhibition (25). Our current understanding of the nature of ENaC gating mechanisms provides no unequivocal answers to the question of how the aforementioned domains affect self-inhibition.CPT-cGMP, but not parent cGMP, acutely activated human ENaC activity as an external ligand (19,26). The aim of this study was to examine whether CPT-cGMP could be used as a pharmaceutical strategy to up-regulate alveolar fluid clearance (AFC) via stimulating ENaC and its underlying mechanisms.…”
mentioning
confidence: 99%
“…However, novel functions of PKG II have been identified, including an involvement in mechano-signal transduction in osteoblasts, and in the regulation of sodium channels (20,21). In addition, previous studies have indicated that PKG II may be a potential cancer suppressor due to its role in the regulation of proliferation and apoptosis in cancer cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data show that this kinase has some new functions: Nie et al (18) found that PKGII regulated epithelial sodium channels; Rangaswami et al (19,20) reported that PKGII had an important role in mechano-transduction of osteoblast. A more important finding in research of PKGII is that this kinase has a role in regulating proliferation and apoptosis of cells and is potentially associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%